2007
DOI: 10.1111/j.1440-1843.2007.01205.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulmonary rehabilitation in patients with idiopathic pulmonary fibrosis

Abstract: Effects of pulmonary rehabilitation in patients with idiopathic pulmonary fibrosisNISHIYAMA O, KONDOH Y, KIMURA T, KATO K, KATAOKA K, OGAWA T, WATANABE F, ARIZONO S, NISHIMURA K, TANIGUCHI H. Respirology 2008; 13: 394-399 Background and objective: Although pulmonary rehabilitation is effective for patients with COPD, its efficacy in patients with IPF is unknown. The purpose of this study was to evaluate the effects of pulmonary rehabilitation in IPF. Methods: Thirty patients diagnosed with IPF, according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
302
4
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(330 citation statements)
references
References 45 publications
12
302
4
12
Order By: Relevance
“…Therefore, our data show a significant and clinically important improvement in all sub-and summary-scores of SF-36. Our observation is in concordance with some published studies [8,23,31,33], while others did not detect any influence of PR in HRQL [10,24,25]. NAJI et al [31] demonstrated in their group of ILD patients a significant reduction in anxiety and depression after completing PR.…”
Section: Figuresupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, our data show a significant and clinically important improvement in all sub-and summary-scores of SF-36. Our observation is in concordance with some published studies [8,23,31,33], while others did not detect any influence of PR in HRQL [10,24,25]. NAJI et al [31] demonstrated in their group of ILD patients a significant reduction in anxiety and depression after completing PR.…”
Section: Figuresupporting
confidence: 93%
“…We observed a small, statistically significant improvement of blood gas analysis and lung function parameters, which is in line with other published studies [10,23]. Although these improvements are statistically significant, their clinical relevance is probably negligible.…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…During eight weeks of exercise was performed: continuous exercise on treadmill for 30 minutes starting at 80% speed increase achieved in 6MWT at 4 weeks at 90% [7,8]; O 2 was administered to patients who present in 6MWT desaturation ≥ 4% or during exercise O 2 saturation [SpO 2 ] was <90%; upper limb muscle strengthening 4 sets of 12 reps with 1 minute rest at 30% of maximum resistance [RM], increasing to four weeks at 40% of the RM; breathing techniques and mobility of the chest.…”
Section: Methodsmentioning
confidence: 99%